Hamstring Activity Before and After Break-Point Angle Calculated By Smartphone Application During the Nordic Hamstring Exercise - Toshiaki Soga; Shota Yamaguchi; Takayuki Inami; Hiromi Saito; Nadaka Hakariya; Naoto Nakaichi; Sho Shinohara; Koki Sasabe; Hayato Nakamura; Teerapat Laddawong; Kei Akiyama; Norikazu Hirose (International Journal of Sports Physical Therapy)
# INTRODUCTION